Transforming university teaching - Ashwin, P (Centre for Global Higher Education, University of Oxford, 2019)
Working Paper 49 is a transcript of the keynote that Professor Ashwin gave at the fourth annual conference of the Centre for Global Higher Education at the UCL Institute of Education in London on 3 April 2019.